2014 IEEE International Electron Devices Meeting 2014
DOI: 10.1109/iedm.2014.7047163
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Si/TMD 2D electronic double channels fabricated using solid CVD few-layer-MoS2 stacking for V<inf>th</inf> matching and CMOS-compatible 3DFETs

Abstract: Stackable 3DFETs such as FinFET using hybrid Si/ MoS 2 channels were developed using a fully CMOScompatible process. Adding several molecular layers (3-16 layers) of the transition-metal dichalcogenide (TMD), MoS 2 to Si fin and nanowire resulted in improved (+25%) I on,n of the FinFET and nanowire FET (NWFET). The PFETs also operated effectively and the N/P device V th are low and matched perfectly. The proposed heterogeneous Si/TMD 3DFETs can be useful in future electronics.I. Introduction 3DFETs can improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…4c we plot the iterative progresses of FinFETs as a function of time line. It is seen that, strikingly, the W fin has been levelling off since 2 decades 4,6,10,11,18,[22][23][24][25][26][27][28] . Our present work brings this nanostructure to a limit of 0.6 nm ML, an order of magnitude thinner than the W fin of state-of-the-art FinFETs.…”
Section: Discussionmentioning
confidence: 99%
“…4c we plot the iterative progresses of FinFETs as a function of time line. It is seen that, strikingly, the W fin has been levelling off since 2 decades 4,6,10,11,18,[22][23][24][25][26][27][28] . Our present work brings this nanostructure to a limit of 0.6 nm ML, an order of magnitude thinner than the W fin of state-of-the-art FinFETs.…”
Section: Discussionmentioning
confidence: 99%
“…In 2014, a 3D FET with MoS 2 channel covering HfO 2 /Si upstanding Fin structure was demostrated. Low operating voltage down to 1 V and matched V th between the n‐type and p‐type transport regime were realized in the hybrid Si/TMDC FETs with 50 nm channel length and equivalent oxide thickness (EOT) <1 nm . More recently, Chen et al demonstrated an ultra‐scaled U‐shape MoS 2 transistor with self‐aligned Si source/drain and Si topgate (Figure b,c), by a fully CMOS‐compatible process.…”
Section: Introductionmentioning
confidence: 99%
“…To reach high mobility, epitaxial growth of crystalline MoS 2 on a crystal substrate is needed. Unfortunately, the mobility is lower for CVD-grown MoS 2 25 26 27 28 than peeled-off flakes from crystals 21 22 23 24 25 26 27 28 . The lattice mismatch caused defects are the other major concern for circuit yield.…”
Section: Resultsmentioning
confidence: 99%
“…This TFT also showed a high I ON /I OFF of 2.3 × 10 7 , low sub-threshold swing ( SS ) of 0.11 V/decade, low threshold voltage ( V T ) of 0.27 V, low drive voltage of 2.5 V for low switching power, and ultra-thin layer with a thickness of 4.5 nm. Such ultra-thin thickness is comparable with that of multilayered MoS 2 27 for low DC standby power consumption. Notably, Sn (Group IV) has ns 2 np 2 electron configuration and directive sp 3 orbitals, which differ from those of Zn 7 .…”
mentioning
confidence: 88%
See 1 more Smart Citation